Promoting the Wasaṭī Doctrine to Balance between Conservatism and Pragmatism in Post-9/11 America: The Case of Yasir Qadhi - David, Elad Ben (Islam and Christian-Muslim relations, 2024)
Sheikh Dr Yasir Qadhi is one of America’s most famous intellectual senior clerics, and is a member of the generation of young American preachers that burst into Western public awareness during the post-9/11 era. During the 1990s, Qadhi was a hardcore Salafi, but the 9/11 attacks and his doctoral studies on Islamic theology at Yale University (2005–2013), influenced and reformed many of his world views, causing him to adapt a more moderate and pragmatic stance. This article’s main argument is that Qadhi represents a case study of the American Islamic reform mindset in the post-9/11 era, which attempted to reconcile the tension between conservative and pragmatic Islamic trends with contemporary American reality. These clerics try to pave the way for Islam’s essential principles to remain while bravely confronting contemporary issues with new consideration. The article explores Islam in America in the post-9/11 era and a variety of examples of his doctrine relevant to the American Muslim minority. Qadhi’s Islamic rulings manifest his affinity to wasaṭī scholars, such as Sheikh Yusuf al-Qaradawi, which shed light on one of Qadhi’s primary goals – preserving Islam in America and the West for future generations.